Tauroursodeoxycholic acid binds to the G-protein site on light activated rhodopsin - Lobysheva, E. (Exp Eye Res, 2018)
The heterotrimeric G-protein binding site on G-protein coupled receptors remains relatively unexplored regarding its potential as a new target of therapeutic intervention or as a secondary site of action by the existing drugs. Tauroursodeoxycholic acid bears structural resemblance to several compounds that were previously identified to specifically bind to the light-activated form of the visual receptor rhodopsin and to inhibit its activation of transducin. We show that TUDCA stabilizes the active form of rhodopsin, metarhodopsin II, and does not display the detergent-like effects of common amphiphilic compounds that share the cholesterol scaffold structure, such as deoxycholic acid. Computer docking of TUDCA to the model of light-activated rhodopsin revealed that it interacts using similar mode of binding to the C-terminal domain of transducin alpha subunit. The ring regions of TUDCA made hydrophobic contacts with loop 3 region of rhodopsin, while the tail of TUDCA is exposed to solvent. The results show that TUDCA interacts specifically with rhodopsin, which may contribute to its wide-ranging effects on retina physiology and as a potential therapeutic compound for retina degenerative diseases.